PENGARUH BI RATE, INFLASI DAN JUMLAH KANTOR CABANGTERHADAP SIMPANAN MUDHARABAH PADA BANK UMUMSYARIAH TAHUN 2011-2014 - HIDAYANTI, RAHMA (Jurnal Akuntansi AKUNESA, 2015)
Growth and development of conventional banks and Islamic banks can beseen from the increasing number of offices the number of products offered and thenumber of third party funds raised from the public. One of the products offered byIslamic banking is a product using Mudharabah contract. The global economiccrisis in 2008 in Indonesia less impact on Islamic banks because Islamic bankingcould prove that the global economic crisis Islamic bank is able to survive. This issupported by an increase in third party funds DPK Islamic Banks BUS and ShariaBusiness Unit UUS. Economic growth in banking is influenced by the rate ofinflation and the BI rate. This study aims to determine the effect of Bi RateInflation and the amount of the Branch Office of the Deposit Mudharabah IslamicBanks in 2011 until 2014. These results indicate that Bi Rate does not affect theMudharabah Savings. Inflation showed no influence on Mudharabah Savings andfor a number of branch offices shows that the number of branches has aninfluence on Mudharabah Savings due When Islamic Banks expand branchnetwork the customer will be easier to invest.Keywords: Bi Rate Inflation Number of Branches Deposits Mudharabah.